2020
DOI: 10.1097/hs9.0000000000000459
|View full text |Cite
|
Sign up to set email alerts
|

Control of Systemic Iron Homeostasis by the 3’ Iron‐Responsive Element of Divalent Metal Transporter 1 in Mice

Abstract: Supplemental Digital Content is available in the text

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…SLC11A2 in the Caco-2 cultured cell line), and genes with IRE-like elements deviating from the canonical IRE sequence. Interestingly, Tybl et al [82] found that the 3' IRE in SLC11A2 (DMT1) appears to influence transcript abundance in a developmentspecific manner in mice, by promoting transcript expression during postnatal growth and suppressing expression in adulthood. Together with our findings, this demonstrates that the regulation of IRE genes is more complex than commonly appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…SLC11A2 in the Caco-2 cultured cell line), and genes with IRE-like elements deviating from the canonical IRE sequence. Interestingly, Tybl et al [82] found that the 3' IRE in SLC11A2 (DMT1) appears to influence transcript abundance in a developmentspecific manner in mice, by promoting transcript expression during postnatal growth and suppressing expression in adulthood. Together with our findings, this demonstrates that the regulation of IRE genes is more complex than commonly appreciated.…”
Section: Discussionmentioning
confidence: 99%
“…Under conditions of iron deficiency, the IRE in the target mRNA can be recognized and bound by IRPs, but the consequence of IRP binding depends on the position of the IRE on the mRNA of the target genes. If the IRE is in the 5untranslated region (UTR) of the target mRNA, the binding of IRPs may inhibit the translation of the genes, including L-and H-ferritin and FPN1; if the IRE is in the 3 -UTR, the binding of IRPs may stabilize the mRNA, such as that of transferrin receptor 1 (TfR1) (Casey et al, 1988;Müllner et al, 1989) and divalent metal transporter 1 (DMT1) (Tybl et al, 2020). When cellular iron is sufficient, IRP1 binds to a (4Fe-4S) cluster and, therefore, gains aconitase activity and loses the ability to bind IRE, whereas IRP2 is removed by iron and oxygen-mediated proteasome degradation (Salahudeen et al, 2009;Vashisht et al, 2009) to avoid the excessive iron uptake and to promptly store excess intracellular iron and/or export excess iron.…”
Section: Introductionmentioning
confidence: 99%
“…Since DMT1 activity is dependent to acidic pH, we assume that an increase in iron intake due to increase DMT1 activity by diet-induced acid load must be retro-controlled by the local IRE/IRP system. Indeed, iron regulatory protein IRP1 appears to be active in the intestinal compartment [36] and the 3 -UTR region of DMT1-mRNA contains at least one IRE element, which was recently shown to be active [37,38]. The IRE/IRP system also acts on the expression of the FPN by blunting its translation after binding to the 5 -UTR-IRE of the mRNA [37].…”
Section: Discussionmentioning
confidence: 99%